Performance of tractor and tillage implements in clay soil - Saeed Ranjbarian; Mohammad Askari; Javad Jannatkhah (Journal of the Saudi Society of Agricultural Sciences)
A mobile instrumentation system was developed and mounted on an MF 285 tractor to measure the performance parameters of the tractor and attached implements. The system measures implement draft, fuel consumption, real forward velocity, tillage depth and engine speed. Other parameters such as wheel slippage, drawbar power and traction efficiency would be calculated by ASABE standard. Overall energy efficiency for the tractor-implement system was calculated, too. Three implements included of moldboard plow, disk plow and chisel plow at four forward velocities (1.5, 2.3, 3 and 4 km/h) in 23 cm depth and 1500 rpm engine speed was examined. Analysis of variance (ANOVA) of resulted data revealed that increase of forward velocity results in increase of implement draft, wheel slippage, drawbar power and overall energy efficiency but results in decrease of traction efficiency. Furthermore, fuel consumption decreased by increase of velocity from 1.5 km/h to 3 km/h but increased by increase of velocity from 3 km/h to 4 km/h. Moreover, it was observed that draft requirement for implements in tests ranged from 8.2 kN for the disk plow to 13 kN for the chisel plow and fuel consumption ranged from 10.72 L/ha for the chisel plow to 26.5 L/ha for the moldboard plow. The ranges in mentioned parameters indicate that energy saving can be readily done by selecting energy-efficient implements and by proper matching of the tractor size and operating parameters to the implements.